COVID-19: what should we learn? - Pozzi MD, A; Pozzi MD, F; Campione MD, A; Iorio MD, A (International Journal of Medicine, 2020)
At the beginning of 2020 the COVID-19 outbreak had a massive impact on socio-economic, psychology and health system. The authors depict the possible weak points that influenced the spread infection. A collective decision making should be suggested in order to have an unvarying control to counteract future outbreaks, along with the needed of more health resources.Â Â